Sharīʾah-compliant central banking practices: lessons from Muslim countries' experience - Zaheer Anwer; Shabeer Khan; Muhammad Abu Bakar (ISRA International Journal of Islamic Finance, 2020)
Purpose: The purpose of this study is to document how a central bank can perform its primary and secondary functions in a Sharīʿah-compliant manner. It also seeks to investigate the outcomes of the experiments of Muslim-majority countries in this regard. Design/methodology/approach As a first step, a detailed review of existing literature is conducted, which discusses the views of scholars and practitioners on the central banking mechanism in a fully Sharīʿah-compliant financial system. Moving further, the case studies of Iran, Sudan and Pakistan are presented to highlight experiences of regulators from three Muslim-majority countries, which aimed to achieve full compliance with Sharīʿah (Islamic law) principles related to Islamic finance. To evaluate their models, an assessment of their practices is performed in the light of Sharīʿah rules and principles based on existing literature. Finally, the issues involved in establishing a Sharīʿah-compliant central bank (SCCB) are discussed and improvements are suggested. Findings It is found that Iran played an effective role in pursuing broader objectives of monetary policy by setting priorities for credit allocation and assisting the government in reducing expenses; however, with respect to instruments, its experience is limited to the rebranding of conventional products. Sudan has not only used monetary policy to effectively curb inflation but also it has introduced various indirect instruments to perform monetary operations. Pakistan succeeded in formulating a theoretical roadmap to establish a SCCB but the desired objectives could not be achieved because of multiple factors. Practical implications This study has important policy implications for regulators and policymakers from Muslim countries, who can use the findings in shaping effective Sharīʿah-compliant central banking practices in their respective countries. Originality/value This study discusses the salient features of an important Islamic financial institution, the central bank and evaluates the experiments of three Muslim-majority countries in implementing Sharīʿah-compliant central banking practices. To the best of the knowledge, this evaluation has not been performed in the existing literature and the present study fills in this gap.
Keywords: 330; Pakistan; Sudan; Islamicfinance; Monetary policy; Iran; Sharīʿah-compliant central bank